2023
DOI: 10.3390/cancers15061793
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus Laparoscopic Partial Nephrectomy in the New Era: Systematic Review

Abstract: (1) Background: In recent years there have been advances in imaging techniques, in addition to progress in the surgery of renal tumors directed towards minimally invasive techniques. Thus, nephron-sparing surgery has become the gold standard for the treatment of T1 renal masses. The aim of this study is to investigate the benefits of robotic partial nephrectomy in comparison with laparoscopic nephrectomy. (2) Methods: We performed a systematic review according to the PRISMA criteria during September 2022. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…For the LPN series, we observed that the longer the time taken to reconstruct the resection surface, the higher the probability of developing a complication. Guerrrero et al [12] showed similar complication rates for RAPN versus LPN in a recent systematic review, and we believe that a better kidney reconstruction was achieved using a robotic platform, although without any correlation with the rate of complications.…”
Section: Discussionmentioning
confidence: 52%
“…For the LPN series, we observed that the longer the time taken to reconstruct the resection surface, the higher the probability of developing a complication. Guerrrero et al [12] showed similar complication rates for RAPN versus LPN in a recent systematic review, and we believe that a better kidney reconstruction was achieved using a robotic platform, although without any correlation with the rate of complications.…”
Section: Discussionmentioning
confidence: 52%
“…A prospective comparison of RRN with LRN in many cases at multiple centres with long-term oncological results best illustrates the status of RRN versus LRN. Concerning the learning curve of these minimally invasive procedures, surgeons seem to have a longer learning curve with the laparoscopic approach in comparison to the robotic approach as highlighted by Guerrero et al [ 18 ]. Gab Jeong et al mentioned that RRN was linked to longer operative time and higher hospital cost when compared to LRN, but not associated with major post-operative complications [ 19 ].…”
Section: Reviewmentioning
confidence: 99%
“…The American Urological Association guidelines recommend partial nephrectomy as a first-line treatment for tumors between 4 and 7 cm in size—clinically classified as stage T1a or T1b—or for patients with absolute indications such as bilateral renal masses or a solitary kidney ( 2 ). Regardless of the type, nephrectomy has witnessed a significant shift toward minimally invasive surgery (MIS)—comprising laparoscopic and robotic approaches—in recent years due to its numerous advantages over traditional open surgery such as reduced perioperative blood loss and analgesia use, shorter hospital stay, quicker return to full function, and equivalent short- and long-term oncological outcomes ( 3 8 ). Both radical and partial nephrectomies can be performed openly or using minimally invasive laparoscopic and robotic approaches ( 9 ).…”
Section: Introductionmentioning
confidence: 99%